Power line communications in practice - Carcelle, Xavier (Artech House, 2009)
Here's everything you want to know about PLC technology, theory, applications, and installation organized for you in the first definitive English-language book on the subject. You get a solid theoretical grounding on this emerging alternative to Wi-Fi and Ethernet together with best-practice examples of PLC deployments and down-to-business procedures to install PLC in the home, design large-scale PLC networks for businesses and communities, and choose the right technology and equipment for any application. A state-of-the-art reference, how-to guide, and problem-solver wrapped up in one complete source, this benchmark work brings you quickly up to speed on PLC network architecture, functionalities, security issues, and applications. You get details on PLC modems, transformers, and other equipment along with PLC installation and configuration guidelines that cover everything from choosing the topology for a PLC network to configuring parameters under Windows or Linux/BSD. The book spells out steps to install PLC in homes followed by design and configuration procedures for PLC business networks that cover all issues involving network architecture, standard and equipment selection, security, and other essentials. The book also explores the development of community-wide PLC networks and the emergence of hybrid PLC-Ethernet-Wi-Fi applications. Supported by real-world examples and 280 illustrations, this hands-on resource takes you to the cutting edge of power line communications and helps you tap its rich potential moving forward. Publisher abstract.
Description based upon print version of record.
Keywords: Electric lines -- Carrier transmission.; Telecommunication lines.